Relación entre la jefatura del hogar según sexo y la pobreza en el Perú periodo 2015-2019 - Vásquez Castillo, Cinthia Luisa (Universidad Nacional de la Amazonía Peruana, 2022)
The sex of the head of a poor household has a lot to do with the proper use of scarce resources, with women showing the greatest efficiency. The objective of this research is to determine the relationship between the head of the household according to sex and poverty in Peru, in the period 2015 - 2019. Directed for this purpose, the present study of Quantitative type, Correlational level and Non-Experimental design. The research concludes that there is no relationship between the sex of the head of the household and poverty, a conclusion based on the result of the Correlation Coefficient, which was r = 0.19957003; and of the Determination Coefficient R2 = 0.03982820; results that demonstrate the non-existence of statistical association and determination between the aforementioned variables. In this sense, poverty is due to other factors, but not to the sex of the head of the household, despite the fact that a man heads 76.50% of all poor households. The economic activity that mostly occupies women is "Other Services", with 41.40% at the national level and 43.92% in the Loreto region. The occupation category in which women mainly work is "Wage earner", at the national level with 39.40%; and "Independent Worker" in the Loreto region, with 43.70%. The result of employed women by type of sector according to formality indicates that, at the national level, 75.60% do so in the “Informal Sector”; and 83.28% in Loreto.

El sexo del jefe de un hogar pobre tiene mucho que ver con el uso adecuado de los recursos escasos, siendo las mujeres las que muestran mayor eficiencia. El objetivo de la presente investigación es determinar la relación entre la jefatura del hogar según sexo y la pobreza en el Perú, en el periodo 2015 - 2019. Direccionado por este propósito, se lleva a cabo el presente estudio de tipo Cuantitativo, nivel Correlacional y de diseño No Experimental. La investigación concluye que no existe relación entre el sexo del jefe del hogar y la pobreza, conclusión basada en el resultado del Coeficiente de Correlación que fue de r = 0.19957003; y del Coeficiente de Determinación R2 = 0.03982820; resultados que demuestran la inexistencia de asociación estadística y determinación entre las variables antes señaladas. En tal sentido, la pobreza se debe a otros factores, pero no al sexo del jefe del hogar, a pesar de que del total de hogares pobres el 76.50% tiene como jefe a un hombre. La actividad económica que ocupa mayoritariamente a las mujeres es “Otros Servicios”, con el 41.40% a nivel nacional y 43.92% en la región Loreto. La categoría de ocupación en la que laboran principalmente las mujeres es “Asalariado”, a nivel nacional con el 39.40%; y “Trabajador Independiente” en la región Loreto, con el 43.70%. El resultado de las mujeres ocupadas por tipo de sector según la formalidad señala que, a nivel nacional, el 75.60% lo hace en el “Sector Informal”; y el 83.28% en Loreto.
Keywords: Familia; Actividades económicas; Pobreza; Sexo; https://purl.org/pe-repo/ocde/ford#5.02.01; https://purl.org/pe-repo/ocde/ford#5.04.01